2010
DOI: 10.1007/s11999-009-1046-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Patient Outcomes After THA and TKA: Is There a Difference?

Abstract: Both primary total hip (THA) and knee (TKA) arthroplasty relieve pain, restore function, and increase mobility. Despite these successes, there is controversy as to whether THA or TKA provides greater or similar improvement. We therefore compared primary THA and TKA patient results in terms of (1) willingness to have surgery again; (2) WOMAC change score; (3) whether expectations were met; and (4) satisfaction. Patients undergoing primary THA were more willing to undergo their surgery again (THA 96%, TKA 89%), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
149
1
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(165 citation statements)
references
References 12 publications
10
149
1
5
Order By: Relevance
“…Kilgus et al [40] reported that young age of patients does not have a negative effect on the survival of the conversion of a fused hip to THA. We agree with Bourne et al [7] that the patient's opinion regarding outcome is one of the most important issues. Patient satisfaction has been included in the assessment of THA in many studies [9,18,20,25,38,43,47,49].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Kilgus et al [40] reported that young age of patients does not have a negative effect on the survival of the conversion of a fused hip to THA. We agree with Bourne et al [7] that the patient's opinion regarding outcome is one of the most important issues. Patient satisfaction has been included in the assessment of THA in many studies [9,18,20,25,38,43,47,49].…”
Section: Discussionsupporting
confidence: 88%
“…Patient satisfaction has been included in the assessment of THA in many studies [9,18,20,25,38,43,47,49]. Some authors have compared satisfaction after THA with satisfaction after TKA [7], and others have evaluated satisfaction after total joint replacement, pooling THAs and TKAs [46]. The assessment of these procedures is standardized and may be done in a similar way using generic tools for both procedures [11,46].…”
Section: Discussionmentioning
confidence: 99%
“…Although Jones proved that patients > 80 presented 4 ± 2 comorbidities and patients < 80 presented 3.5 ± 2 comorbidities, comorbidity did not have a significant influence on the pain, PF and QOL after TKA and THA (20), as was the case in the current study. On the contrary, Katz (26), Becker (28) and Bourne (29) stated that comorbidity and other factors were the predictors for the outcome of arthroplasty surgery. Therefore, there is controversy on comorbidities and its influence on TKA outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Unresolved pain, residual symptoms, functional limitations, any of a number of postoperative complications, overlapping pain from spine or hip disease, and varying patient pain thresholds all may contribute to lingering dissatisfaction [2,9]. Of the various culprits, unmet patient expectations have been reported to be the most important [2].…”
mentioning
confidence: 99%
“…Of the various culprits, unmet patient expectations have been reported to be the most important [2]. Noise generation from the joint itself can be disturbing, and can lead to unmet expectations, even though it rarely generates any functional problems.…”
mentioning
confidence: 99%